2021
DOI: 10.1007/s12144-021-02111-w
|View full text |Cite
|
Sign up to set email alerts
|

Mindful parenting: a Meta-analytic review of intrapersonal and interpersonal parental outcomes

Abstract: Mindfulness-based programs (MBPs) are increasingly used to reduce parental stress and to enhance dyadic interactions between parents and children. Prior reviews examining the effects of MPBs for parents have assessed restricted target populations, limited outcomes measures, and have relied on uncontrolled studies. This systematic and meta-analytic review quantified the efficacy of MBPs for parents using comprehensive intrapersonal and interpersonal outcome measures and methodologically robust studies. Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Mindful parenting also showed promising results in improving the well-being of parents of children with autism spectrum disorder [10]. In addition, the positive effects of mindful parenting on parents' well-being were more evident in parents of children with medical than psychological conditions [7]. However, despite the promising results of mindfulness-based interventions in promoting parents' mental health of children with developmental disorders, these reviews and metaanalyses suggested caution due to the small number of studies carried out [8].…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mindful parenting also showed promising results in improving the well-being of parents of children with autism spectrum disorder [10]. In addition, the positive effects of mindful parenting on parents' well-being were more evident in parents of children with medical than psychological conditions [7]. However, despite the promising results of mindfulness-based interventions in promoting parents' mental health of children with developmental disorders, these reviews and metaanalyses suggested caution due to the small number of studies carried out [8].…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
“…Mindful parenting interventions have been proposed to support parents of children and adolescents with typical, at-risk, and atypical development, improving intrapersonal and interpersonal outcomes [7]. The following paragraph mainly summarises the findings of reviews and meta-analyses.…”
Section: Mindful Parenting Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most known and researched interpersonal applications of mindfulness is mindful parenting, which refers to the ability to bring nonjudgmental, present-centered awareness to parent–child interactions and the experiences of parenting (Duncan et al, 2009 ). Numerous studies found that training in mindful parenting improves the quality of parenting behaviors (Gannon et al, 2017 ) and reduces parental stress (see Anand et al, 2021 for a review) as well as improves parent-adolescent relationship quality, social skills and quality of life of children, and decreases children psychopathology symptoms and problem behaviors including aggressive behaviors (Bögels et al, 2014 ; Coatsworth et al, 2015 ; Dehkordian et al, 2017 ; Meppelink et al, 2016 ; Singh et al, 2006 , 2007 , 2010 ; Turpyn & Chaplin, 2016 ). In a recent study, mindful parenting training with mothers and their babies showed positive effects on both the mothers and babies (Potharst et al, 2017 ; for a review/meta-analysis, see Townshend et al, 2016 ).…”
mentioning
confidence: 99%